Strategi Pengembangan Model Bisnis Koperasi Serba Usaha Pinto Jaya: Strategy of Business Development at Koperasi Serba Usaha Pinto Jaya - Andreas, David; Nurrochmat, Dodik Ridho; Djohar, Setiadi (Jurnal Aplikasi Bisnis dan Manajemen, 2020)
Koperasi as an association for mutual welfare, conducts business and activities to fulfill the needs of the members. Koperasi Pinto Jaya located at Cipinang Melayu, East Jakarta, was established in 2011. The aim of this study is to design a business model in the future as a step towards further development of KSU Pinto Jaya. This research using descriptive qualitative with approaching method of business model canvas (BMC) and equipped with SWOT and blue ocean strategy. Respondents include internal and external respondents. Internal respondents are the chairman of the cooperative, supervisor, manager, head of the savings and loan unit and cooperative members with the qualifications as respondents. The external respondent is the chairman of the PT. Chingluh and Department of cooperatives and small and medium enterprises. The results obtained from this research is the idea which driven from several central innovation point, including the key activities where KSU Pinto Jaya forms a trading unit business which purposes meeting the need of the member and increasing the revenue. While the next idea as a starting point to form an innovation that starts from the addition of key resources to support and increase key activities. The official website and computer application development carried out by KSU Pinto Jaya becomes starting point to form business model ideas based on conditions where the utilization of information technology by KSU Pinto Jaya is not optimized yet. Keywords: business model canvas, blue ocean strategy, SWOT analysis, Pinto Jaya